Preoperative Visual Loss is the Main Cause of Irreversible Poor Vision in Children with a Brain Tumor - Goldenberg-Cohen, Nitza; Ehrenberg, Miriam; Toledano, Helen; Kornreich, Liora; Snir, Moshe; Yassur, iftach; Cohen, Ian J.; Michowiz, Shalom (Frontiers in Neurology, 2011)
The purpose of this study was to characterize the severe postoperative irreversible visual loss induced by optic neuropathy in some children with a brain tumor. The computerized database (2003–2008) of a neuro-ophthalmology service of a major pediatric tertiary center was reviewed for all children with severe irreversible visual loss (counting fingers or less) due to brain-tumor-related optic neuropathy at their last follow-up examination. Data on age, gender, etiology, initial symptoms, and signs, visual acuity before and after surgery and at last examination, neuroimaging findings, and treatment were collected. Of 240 children, 198 were operated. Of those, 10 (5%, 5 boys and 5 girls) met the study criteria. Data for the initial visual examination were available for eight children: one had binocular blindness (uncertain light perception, counting fingers); three had monocular blindness already at diagnosis (no light perception, counting fingers, no fixation); three had 6/60 vision in the worse eye; and one had good vision bilaterally (6/10). Four children had direct optic nerve compression, four papilledema, and three gliomas. Four children (40%; with craniopharyngioma, pineal germinoma, or posterior fossa tumor) exhibited a rapid deterioration in vision after tumor depression (one direct optic nerve compression and three increased intracranial pressure); two had monocular visual loss postoperatively; vision remained stable in four (after ≥5 follow-up visits), but did not improve. This study shows that tumor-related optic neuropathy may be associated with marked visual loss inspite of successful tumor resection; in 40% of children, the deterioration occurs perioperatively. Direct compression is the main cause of visual loss, while papilledema usually resolved without visual sequelae. However, autoregulatory changes may be responsible for rapid visual loss following decompression for chronic papilledema. Clinicians need reminding about the problem of postoperative visual loss and we speculate on how it can be avoided.